Profibus protocol extensions for enabling inter-cell mobility in bridge-based hybrid wired/wireless networks - Ferreira, Luís (2014)
Future industrial control/multimedia applications will increasingly impose or benefit from wireless and mobile communications. Therefore, there is an enormous eagerness for extending currently available industrial communications networks with wireless and mobility capabilities. The RFieldbus European project is just one example, where a PROFIBUS-based hybrid (wired/wireless) architecture was specified and implemented. In the RFieldbus architecture, interoperability between wired and wireless components is achieved by the use specific intermediate networking systems operating at the physical layer level, i.e. operating as repeaters. Instead, in this paper we will focus on a bridge-based approach, which presents several advantages. This concept was introduced in (Ferreira, et al., 2002), where a bridge-based approach was briefly outlined. Then, a specific Inter-Domain Protocol (IDP) was proposed to handle the Inter-Domain transactions in such a bridge-based approach (Ferreira, et al., 2003a). The major contribution of this paper is in extending these previous works by describing the protocol extensions to support inter-cell mobility in such a bridge-based hybrid wired/wireless PROFIBUS networks.